Kemampuan Literasi Membaca Siswa Indonesia (Berdasarkan hasil UN dan PISA) - Liestari, Suci Paramitha; Muhardis, NFN (Indonesian Journal of Educational Assessment, 2020)
National Literacy Movement (GLN) in Permendikbud No. 23/2015 requires Indonesian students to master at least six basic literacies. One of them is literacy. This literacy is the initial literacy that must be mastered because it includes functional literacy that is useful in everyday life. This literacy is not only how a people is free from illiteracy, but also has the life skills to be able to compete globally. This year is the fifth year since the program was launched. Ideally, a change in literacy ability can be seen in students. National Examinations, especially Indonesian Language test, can be used as a benchmark for these achievements. This test requires students to be able to answer problems related to reading and writing (literature and non-literature). Remarkably, for three consecutive years, the results of the Indonesian Language National Examination, especially at the Junior High School level, were ranked highest compared to other subjects. In general, students' literacy reading ability is in the ability to access and retrieve information in simple texts (150 to 200 words). They are able to determine the main sentence / main idea of a paragraph, determine the main character, and determine the background evidence of place / time / situation in the text. This is comparable to the 2018 PISA study, that is, the literacy ability of Indonesian students reading is at the level of detecting and handling conflict and representing information literally in the form of uncomplicated questions. Unfortunately, there are some abilities that students have not mastered based on the results of the two tests. In this paper these matters are discussed more deeply with the aim of becoming an enrichment material for teachers in schools to further enhance students' literacy reading skills.